Electrocardiographic Modifications In Hypertensive Patients Without Associated Diseases - Ferrer-Orozco, Lissett; Orozco-Martínez, Yoandri; Medina-Morales, Jesús Ignacio; Orozco-Pérez de Prado, Beatriz Isabel; Orozco-Pérez de Prado, Calixto Emanuel; Hernández-Maldonado, Rosa María; Chávez-González, Elibet (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: High Blood Pressure is considered a devastating disease due to its several complications, which do not manifest until there is severe damage established, reason why the electrocardiogram can be a tool easily accessible in clinical practice to detect cardiac complications that may happen in the future allowing us to act early in their treatment. Objective: Identify the electrocardiographic modifications present in hypertensive patients without associated diseases. Methods: An analytical observational study of case-control in hypertensive patients without associated diseases or supposedly healthy patients, belonging to the Family Medical Office # 17.30, of the "Chiqui Gómez Lubián" Polyclinic; Santa Clara municipality was carried out in the period from November 2017 to February 2018. Results: Maximum P-wave mean was significantly higher in the case group (56.43 ms vs 35 ms control group, p= 0,000), behaving similarly when comparing P-wave dispersion in both groups (56, 43 ± 19, 48 ms vs 35, 00 ± 16, 98 p=0,001). Maximum corrected QT interval showed significant differences between both groups (471, 75 ±32, 04 ms vs 448, 36 ±40, 84 ms, p= 0,020), QT dispersion did not showed significant differences. The maximum JT segment and its dispersion did not showed to be significantly different. Conclusions: P wave dispersion, maximum P wave, maximum QRS, its dispersion and the maximum QT interval showed significant differences between both groups; those results were findings on hypertensive patients group. On this sample the increase QT intervals could be dependent on QRS but not on the JT interval.